EFFECTIVE ASPECTS OF THE HOLISTIC APPROACH IN PRIMARY EDUCATION - Khujanazarova Gulbakhor Gofurjonovna; Nurmatjonov Tojimuhammad Shavkatjonovich (Modern American Journals, 2025)
The “Uzbekistan-2030” strategy sets the task of improving the quality of primary education by 2030, based on international criteria and advanced foreign experience. On this basis, the introduction of an inclusive education approach to the primary education system in our country and the development of knowledge and skills of children with special educational needs through it is defined as an important strategic direction.
Keywords: primary education, innovative approaches, Uzbek education system, inclusive education, student qualifications, pedagogical problems, teacher training, experience and analysis, equal opportunities, efficiency.